Kepemimpinan Pendidikan Masa Depan dan Kekinian Berbasis Agama, Filsafat, Psikologi dan Sosiologi;Implementasinya dalam Lembaga Pendidikan - Nandang Koswara; Wiwik Dyah Aryani; Lia Yulianti; Armiyanti Armiyanti; Nova Rati Lova (STKIP PGRI SITUBONDO, 2023)
This study aims to examine the future educational leadership model based on the perspectives of religion, philosophy, psychology, and sociology, as well as their implications in educational institutions. The locus of this research is the Prince SMPN 1 Purwakarta Jawa Barat. This study uses a qualitative approach with descriptive analysis method. Interviews were conducted directly with informants, consisting of the school principal, the vice principal, and educational staffs in the educational institution. The results of observations and documentation were obtained from various studies of documents, manuscripts, and archives related to the implementation of educational leadership at SMPN 1 Purwakarta Jawa Barat. The results of the study indicate that the educational leadership model for the future in SMPN 1 Purwakarta after direct interviews with all parties involved in educational institutions can be explained in the discussion of this study